RADICALISM IN ISLAMIC HISTORY - Rokhmah Ulfah (TAWASUT, 2013)
Islam is love and peace religion that brings justice, equality and moderation. The word Islam comes from  salima means surrender, submission and peace. So that being a Muslim means spread and build a peace in the world. In fact nowadays, Islam has appeared as a violent religion bringing hatred. Indeed, this has blotted Islamic message namely peacefulness. Radical movement has a deep historical root in Islam called khawarij. Khawarij emerged when the arbitration (tahkim) conducted between Ali bin Abi Thalib and Muawiyah in Shiffin war and it was a fundamentalist religion movement. The coming  out of Wahabi with their militan followers shows neo-khawarij, radical movement in Islam.Keywords:  violence, extremism, conflict, radicalism